Examination of the Correlation between Dynamic Balance and Leg Strength of 11 and 12-Year-Old Children Who Have Fencing Training - Gülaç, Meryem (Asian Journal of Education and Training, 2019)
In this study, it is aimed to examine the relationship between leg strength and dynamic balance of children who have fencing training. 59 epee athletes who are 11 and 12 years old (33 11-year-old, 26 12-year-old) participated in research groups. Star Excursion Balance Test was used to determine balance performances and Baseline brand leg-dynamometer used to determine the leg strength of athletes who had fencing training. First, the Shapiro-Wilk test was used to determine if the data obtained during the study had a normal distribution. Pearson Correlation test was performed for all data displaying a normal distribution. Significance levels were taken as P<0,05 According to the research findings it was determined that there is a meaningful relationship between leg strength and balance test of athletes who have fencing training. As a result, it was seen that balance test values increase as the leg strength increases.